Uji variabilitas suhu flux pendingin terhadap kinerja mesin stirling - Siregar, Zufri Hasrudy; Refiza, Refiza; Rambe, Fajar Noer (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2023)
Energy is becoming increasingly crucial to the needs of modern man12, so well-being depends mainly on the amount and quality of energy used directly or indirectly. Using a sterling engine is an alternative to using a fuel engine. The purpose of the study is to determine the engine's efficiency by varying the temperature of the fluid analyzed against the performance of the Stirling machine. It was concluded that the amount of heat received by the highest cooling air was 78.03243 J at a cooling air temperature of 38°C and 22.2638 J at a cooling fluid temperature of 30°C, meaning that the greater the cooling fluid temperature, the greater the amount of heat received by the cooling air, The highest radiator effectiveness value was 87.11 per cent at a cooling fluid temperature of 38 degrees Celsius, and the lowest effectiveness value was 57.8 per cent at 30 degrees Celsius. Thus, it can be concluded that the higher the temperature of the cooling fluid, the greater the effectiveness of the radiator; the highest performance of the Stirling engine occurs at 38°C, with a torque of 0.647558672 N.m, power of 17.69898043 W, and efficiency of 75.5%. The lowest Stirling engine performance occurred at 30°C, with 0.592975889 N.m of torque, 14.84101331 W of power, and 71.1% efficiency.